1988
DOI: 10.1002/cne.902780409
|View full text |Cite
|
Sign up to set email alerts
|

Central trajectories of type II spiral ganglion neurons

Abstract: Previous attempts to trace the central pathways of the thin axons from type II spiral ganglion neurons have been hampered by technical difficulties such as fading of the reaction product as distance increases from the injection site (Ryugo et al.: Soc. Neurosci. Abstr. 12:779, '86; Brown: J. Comp. Neurol. 260:591-604, '87). By using small rodents (gerbils and mice), which have short auditory nerves, we have succeeded in filling the entire central axon and terminals of type II neurons after peripheral injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 33 publications
7
96
0
Order By: Relevance
“…1). Fibers with these characteristics have been traced back to parent fibers and cell bodies of origin and confirmed to be type II in previous studies (Brown et al 1988a;Brown and Ledwith 1990;Berglund and Brown 1994;Berglund et al 1996). These studies also suggest that the complete extent of the type II projection into the cochlear nucleus is revealed with HRP labeling.…”
Section: Light Microscopic Observationssupporting
confidence: 70%
See 2 more Smart Citations
“…1). Fibers with these characteristics have been traced back to parent fibers and cell bodies of origin and confirmed to be type II in previous studies (Brown et al 1988a;Brown and Ledwith 1990;Berglund and Brown 1994;Berglund et al 1996). These studies also suggest that the complete extent of the type II projection into the cochlear nucleus is revealed with HRP labeling.…”
Section: Light Microscopic Observationssupporting
confidence: 70%
“…1) and terminate in the cochlear nucleus (Lorente de No 1933;Fekete et al 1984;Brown et al 1988a). Type I fibers have an excitatory influence on their postsynaptic targets, leading to discharge of cochlear-nucleus neurons (Pfeiffer 1966;Golding et al 1995;Kopp-Scheinpflug et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The granule cell domain of the cochlear complex was shown to receive projections from a number of auditory and non-auditory nuclei, and from the thin and unmyelinated type II auditory nerve fibers (Brown et al, 1988). Furthermore, Doucet and Ryugo (1997) showed that microneurons of the granule cell domain projected to the DCN.…”
Section: Discussionmentioning
confidence: 99%
“…Type I and type II axons arborize in parallel to the dorsal and ventral cochlear nuclei in the brainstem; but only type II endings are found within the small cell cap and granule cell layers that envelope the principal nuclei (28)(29)(30)(31)(32). The granule cell domain is thought to be a site for multimodal integration as well as the target of collaterals from olivocochlear efferents (29,30,(33)(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%